Analysis of Legal Change for Women Traveling Without Mahram: A Case Study of the Kingdom of Saudi Arabia Royal Decree No. M/134 of 2019 - Firqah Annajiyah Mansyuroh (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2019)
This paper departs from the problem of why the government of Saudi Arabia changed its policy on women's rights in the public sphere by using case study No. Royal Decree No. M / 134 of 2019 concerning the lifting of the ban on women traveling without a mahram. This is interesting because Saudi Arabia is a country that is notorious for not allowing women to travel without male relatives. This is due to the social conditions of Saudi Arabia's society which are very closely related to the culture of the Patriarchy which constructs the thought of the division of roles between women and men. Seeing this fact, a comprehensive explanation is needed to explain the reasons behind the Saudi government's decision in the current situation. This research explores the factors that hold up the decision made using the feminism approach and analyzes the relationship between social change theory and legal reform. The main factor of women's freedom to travel without mahram is undeniably driven by the influence of economic and social changes. This is because the Saudis want their 2030 Vision to be achieved.